Early childhood mathematics education research [ learning trajectories for young children - Sarama, Julie; Clements, Douglas H. (Studies in mathematical thinking and learning, 2009)
Synthesizes relevant research on the learning of mathematics from birth into the primary grades from the full range of these complementary perspectives.